Ophthalmologic manifestations of adult patients with cystic fibrosis. Issue 2 (March 2022) - Giannakouras, Panagiotis; Kanakis, Menelaos; Diamantea, Filia; Tzetis, Maria; Koutsandrea, Chrysanthi; Papaconstantinou, Dimitrios; Georgalas, Ilias
Introduction: Cystic fibrosis (CF) is the most common life-shortening recessive genetic disease in Caucasians, affecting primarily the lungs. The objective of our study was to investigate potential ophthalmologic involvement in adult patients with CF. Methods: Fifty adult patients with cystic fibrosis and 60 age- and sex-matched controls underwent complete ophthalmologic examination including tear-film Break-Up Time (BUT), Macular Thickness, and peripapillary Retinal Nerve Fiber Layer (pRNFL) thickness measurements using Spectral Domain-OCT. Results: CF patients had significantly lower nasal-inferior pRNFL thickness (median 82 IQR 67–102 vs 92.5 IQR 82–107, p  = 0.005) and lower percentage of normal tear Break-Up Time (56.0% vs 96.7%, p  = 0.001) than healthy controls. All CF patients with BUT <10 s were diagnosed with blepharitis at the time of our assessement. The subgroup of patients homozygous for the most common CF mutation, F508del, had lower nasal-inferior pRNFL thickness ( p  = 0.014) and lower percentage of normal tear Break-Up Time ( p  = 0.001) compared to the control group. Additional findings, present in the CF group only, were punctuate retinal hemorrhages (four patients), vessel tortuosity (four patients), snail-track degeneration, and retinal tufts (two patients without refractive error). There were no significant differences in visual acuity, refractive errors, gonioscopic findings, or intraocular pressure between the groups. Conclusions: Our study is, to the best of our knowledge, the largest ophthalmologic study of patients with cystic fibrosis. We found that CF patients had significantly decreased inferior-quadrant peripapillary retinal nerve fiber layer thickness and decreased tear-film break-up time compared to controls. We highlight the importance of careful regular ophthalmologic assessment and follow-up of these patients.